Mt. Dioxin - Reis, John C; Tsang, Edmund (Online Ethics Center, 2006)
An abandoned wood-treating facility must undergo a Superfund cleanup. The case history and other data are presented in order to provide insight into numerical and ethical problems in this situation. This case is suitable for a junior level fluid mechanics class, or a senior level course on ethics and professionalism.
Case Study / Scenario|Technical / Numerical Case
Keywords: Employer/Employee Relationships; Engineer/Client Relationships; Environmental Justice; Ethics and Society; Research and Practice; Risk; Social Justice; Sustainability; Workplace Ethics